Estimation of static stability and control derivatives using wind tunnel and semi-empirical method [electronic resource] - Mohd. Amirullah Shamsuddin, 1989- (2011)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2011